Rheological Properties Comparing Hot and Cold Bituminous Mastics Containing Jet Grouting Waste - Rosa Veropalumbo; Francesca Russo; Nunzio Viscione; Salvatore A. Biancardo (Advances in Materials Science and Engineering)
The use of reclaimed asphalt pavement is a practice that is adding significant environmental value to road technologies, not only due to the reduction of materials sent to landfill but also because of the mechanical properties of the reclaimed asphalt (RA) that can be reused. This research focuses on the rheological properties of hot and cold bituminous mastics made up as follows: (1) hot mastics mixed with limestone filler (LF) and bitumen, (2) hot mastics, made from bitumen mixed with jet grouting waste (JW), a mixture of water, cement, and soil derived from land consolidation work in underground tunnels, and (3) hot mastics mixed with LF and JW as filler and bitumen. Three different ratios (0.3, 0.4, and 0.5) of filler per unit of neat bitumen (B50/70) were studied. The same number was used for mixing cold mastics, by using an appropriate laboratory protocol designed since the adoption of a cationic bituminous emulsion. A total of 18 mastics were prepared and investigated. The comparison was carried out using the frequency sweep (FS) test, analysing shear modulus G∗, applying the multistress creep and recovery (MSCR) test (40°C and 60°C) as well as the delta ring and ball (ΔR&B) test, focusing on two main issues: (1) the stiffening effect caused by the filler type used for mixing each mastic, and (2) a comparison, in terms of stiffening effects and nonrecoverable creep compliance (Jnr) of hot and cold mastic performance to highlight JW reuse in mastics. The results showed that the best G∗ performance at test temperatures higher than 30°C is given by cold mastic after 28 days of curing time when JW is added to LF and bitumen. The lowest Jnr value was 40°C and 60°C for the same mastic.